Testing for identification in SVAR-GARCH models: Reconsidering the impact of monetary shocks on exchange rates - Helmut Lütkepohl; George Milunovich (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Changes in residual volatility in vector autoregressive (VAR) models can be used for identifying structural shocks in a structural VAR analysis. Testable conditions are given for full identification for the case where the volatility changes can be modelled by a multivariate GARCH process. Formal statistical tests are presented for identification and their small sample properties are investigated via a Monte Carlo study. The tests are applied to investigate the validity of the identification conditions in a study of the effects of U.S. monetary policy on exchange rates. It is found that the data do not support full identification in most of the models considered, and the implied problems for the interpretation of the results are discussed.
Keywords: C32; 330; structural vector autoregression; conditional heteroskedasticity; GARCH; identification via heteroskedasticity